ANALYSIS OF MANAGEMENT ELEMENTS AND MEDICAL RECORD PROCESSING SYSTEM AT BHAYANGKARA HOSPITAL PEKANBARU - Nur'aina Basir; Budi Hartono; Aldiga Rienarti Abidin; Endang Purnawati Rahayu; Abdur Rahman Hamid (The Indonesian Journal of Public Health, 2022)
Introduction: Processing of medical records in hospitals is to support the achievement of administrative order in order to achieve the goals of the hospital, namely improving the quality of health services in hospitals. The results of preliminary observations in processing medical record files at Bhayangkara Hospital were that there were several obstacles including the not yet done assembling, indexing and analyzing medical records and delays in returning medical record files. The aim this study was to determine the elements of man, money, methods, materials, machines in the medical record processing system at Bhayangkara Hospital to improve the quality of medical record services at the hospital. Methods: Qualitative Research and informants:  This study amounted to eight people. The number of human resources is insufficient and have never attended training. Standard operating procedures have never been socialized and existing policies need improvement. Result: Coding activities are often constrained by doctors' writing and completeness of diagnoses and medical actions. Retrieval activities are often constrained by medical record files that are still in the inpatient room and in the case mix room. Conclusion: Overall from the research results, the implementation of medical record processing is not appropriate and must be regulated according to existing guidelines in order to produce medical records that are accurate, readily available, usable, easy to trace back and have complete information so as to create quality information and it is recommended to use electronic medical records.